Analisis Efektivitas, Efisiensi, dan Kontribusi Mobil Yan Starpa dalam Penerimaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan Terhadap Pendapatan Asli Daerah Kabupaten Buleleng Tahun 2020-2021. - Sanjaya, Gusti Ngurah Alit; Erni Sulindawati, Ni Luh Gede (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to determine the effectiveness, efficiency and contribution of Yan Starpa car in the acceptance of PBB-P2 (Rural and Urban Land and Building Tax). Through the results of interviews with two employees and the results of the data obtained at BPKPD Buleleng Regency, with the results of an average effectiveness of 106.95% classified as very effective, an average efficiency of 0.51% classified as very efficient, and an average contribution of 99.99% classified as very good. So that Yan Starpa's car plays a very important role in receiving (PBB-P2) Rural and Urban Land and Building Taxes. The presence of the Yan Starpa Car is highly appreciated by the people who are involved in achieving targets and increasing every year, although there are several obstacles faced by the BPKPD in the PBB-P2 Tax Revenue in the Yan Starpa Car, one of which is the blankspot that hinders the collection of PBB-P2.